Species Diversity and Spatial Distribution of Some Oribatid Mites in Bory Tucholskie National Park (N Poland) - Wojciech Niedbała; Agnieszka Napierała; Jacek Wendzonka; Karolina Lubińska; Marta Kulczak; Jerzy Błoszyk (Diversity)
There are 23 national parks in Poland, and only a few of them have been studied thoroughly with regard to acarofauna so far. One of the least-examined areas in this regard is Bory Tucholskie National Park (BTNP), established in 1996. The aim of this research study was to explore the species diversity, community structure, and spatial distribution of mites from the order Oribatida: ptyctimous mites (Acari: Oribatida) and species from the families Nothridae and Camisiidae (Acari: Oribatida: Crotonioidea) inhabiting different forests open and unstable microhabitats in the area of Bory Tucholskie National Park (BTNP). In the case of ptyctimous mites, the communities were compared to those in other Polish national parks. Based on the analysis of 285 samples collected in BTNP between 2022 and 2024, 8 species of Crotonioidea with dominant Heminothrus peltifer (C. L. Koch, 1839) and 21 species of ptyctimous mites with the most numerous Atropacarus (Atropacarus) striculus (C. L. Koch, 1835) were identified in the analyzed material. The highest species diversity was observed in different types of pine forests (25 species) and in alder forests (24 species), while the lowest diversity occurred in areas with reeds (11 species). The comparison of the number of ptyctimous mites in Polish national parks revealed that BTNP can be ranked second in terms of species diversity among 12 national parks examined in Poland so far.